Pengaruh Pemberian Insentif dan Komitmen Pegawai terhadap Kepuasan Kerja di Unit Pelaksana teknis Pelayanan Persampahan Dinas Lingkungan Hidup Bululawang - Irmania Ulan Nuari; Andi Nu Graha; Sri Wilujeng (Jurnal Riset Mahasiswa Manajemen, 2018)
This study aims to determine the effect of giving incentives and employee commitment to job satisfaction in UPT PP Environmental Service Bululawang. The population in this study amounted to all employees in UPT PP Department of the Environment of Bululawang, amounting to 40 people. Data analysis method used in this research is quantitative analysis. Analysis of the data used is the instrument test through validity and reliability, then the classical assumption test and multiple linear regression analysis to test the hypothesis through the F test and t test. In accordance with the research and discussion conducted by researchers, several conclusions are obtained that (1) Providing Incentives (X1), and Employee Commitments (X2), simultaneously affect Job Satisfaction (Y) UPT PP DLH Bululawang. The magnitude of this simultaneous influence explains that the Employee Incentive and Commitment Commitment can explain or clarify Job Satisfaction at the UPT Bululawang Environmental Service. of 61.1% while the remainder while the remaining 38.9% is explained by other factors that influence job satisfaction of course beyond research variables; (2) the variable Giving Incentives (X1) partially has a significant effect on job satisfaction (Y) indicated by t arithmetic> t table that is 2.338> 2.021 and sig value 0.022 <0.05 and (3) employee commitment (X2) partially as well the most significant effect on Job Satisfaction is indicated by t arithmetic> t table that is 2.722> 2.021 and sig value of 0.000 means that the hypothesis is accepted.